A efetividade jurídica das cláusulas de proteção ambiental nos contratos bancários de concessão de crédito rural em prol do Environmental, Social and Governance (ESG) - Linhares, Natália Ribeiro (My University, 2025)
This study is developed within the context of the global movement for the consolidation of corporate sustainability, with an emphasis on the strategic role of the banking sector in the face of its social and environmental responsibilities. The research analyzes the environmental protection clauses included in rural credit agreements, questioning their effectiveness in light of ESG (Environmental, Social and Governance) principles and investigating the extent to which such provisions have actually been monitored, enforced, and implemented by Brazilian financial institutions. The evolution of the ESG concept, its incorporation into rural credit policies, and the institutional control mechanisms adopted by banks are examined, identifying regulatory and operational limitations that undermine the transformative potential of these agreements. The dissertation also presents an analysis of current legislation and concrete contractual practices, aiming to propose regulatory and operational guidelines that reinforce the legality, transparency, and enforceability of environmental obligations within the sector. The methodology used is qualitative, with an analytical approach, a hypothetical-deductive method, and based on in-depth bibliographic and documental review, allowing the construction of a comprehensive overview of the application and monitoring of environmental clauses in banking contracts. The findings reveal a gap between institutional discourse and the practical effectiveness of ESG clauses, underscoring the need for technical, legal, and regulatory improvements so that rural credit agreements may fulfill their ecological function and contribute meaningfully to sustainable development in Brazil. [resumo fornecido pelo autor]
O estudo desenvolve-se no contexto do movimento global pela consolidação da sustentabilidade corporativa, com ênfase na atuação estratégica do setor bancário diante de suas responsabilidades socioambientais. A pesquisa analisa as cláusulas de proteção ambiental inseridas nos contratos de concessão de crédito rural, problematizando sua efetividade à luz dos princípios do ESG (Environmental, Social and Governance) e questionando em que medida tais dispositivos têm sido, de fato, fiscalizados, exigidos e implementados pelas instituições financeiras brasileiras. Investiga-se a evolução do conceito de ESG, sua inserção nas políticas de crédito rural e os mecanismos institucionais de controle utilizados pelos bancos, identificando limites normativos e operacionais que comprometem a função transformadora dos contratos. A dissertação realiza ainda uma análise da legislação vigente e das práticas contratuais concretas, com o objetivo de propor diretrizes normativas e operacionais que reforcem a juridicidade, a transparência e a exigibilidade das obrigações ambientais assumidas no setor. A metodologia adotada é qualitativa, com abordagem analítica, método hipotéticodedutivo, e base em revisão bibliográfica e documental aprofundada, permitindo a construção de um panorama sobre a aplicação e a fiscalização das cláusulas ambientais em contratos bancários. Como resultado, tem-se a constatação de que há um descompasso entre o discurso institucional e a efetividade prática das cláusulas ESG, sendo imprescindível o aprimoramento técnico, jurídico e regulatório desses dispositivos para que o contrato de crédito rural cumpra sua função ecológica e contribua de forma concreta para o desenvolvimento sustentável no Brasil. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Responsabilidade ambiental; Crédito agrícola; Proteção ambiental; Environmental law; Environmental responsibility; Agricultural credit; Proteção ambiental